PENGARUH KREDIBILITAS SUMBER TERHADAP SIKAP, KEPERCAYAAN SERTA MINAT NASABAH UNTUK MENABUNG PADA PD. BKK DEMPET KABUPATEN DEMAK - Rusyadi Yogo Kusumo, 11.42.02.0019 (Students Journal of Accounting and Banking, 2013)
This study aimed to analyze the effect of source credibility, attitudes, beliefs, and interests customers to save on PD.BKK Dempet Kab. Demak. Research design conducted laboratory experiments which experiments are conducted in an artificial environment or regulated. The selected participants are adults. Based on demographic characteristics of adult consumers are consumers aged over 20 years as many as 65 people, whereas for participants check manipulation as many as 35 people. This study uses a questionnaire to the two versions of the ads while testing instruments for analysis studies to test the validity and reliability testing of the questionnaire and the analysis of variance (ANOVA) to test hypotheses 1 and 2 as well as regression analysis to test hypotheses 3 and 4. The results show that advertising is manipulated from the high and low source credibility Â this will affect consumer attitudes, but had no effect on consumer confidence. Consumer confidence is not influenced by advertising, because confidence in the banking sector is a major factor that led to consumers interested in saving money. While the test results with regression analysis showed that the variables that influence customer interest saving is not just beliefs while attitudes affect the interest of saving money, where the higher the influence of the variables of trust, the higher the perceived interest of saving money. Â Keywords: source credibility, advertising, attitudes, confidence, interest to save